Climate change perceptions and adaptive responses of small-scale farmers in two Guatemalan landscapes - Viguera, Bárbara (2019)
Introduction. The productivity of certain crops such as coffee (Coffea arabica L.), maize (Zea mays) and beans (Phaseolus vulgaris L.) is expected to decline in Central America because of climate change. This will impact regional economies and livelihoods of smallholder farmers relying on these crops for their food security and livelihoods. There is a need to understand how climate change is already impacting smallholder farmers in Guatemala in order to promote adaptation measures that will allow them to face these impacts. Objective. The objectives of this study were to characterize two Guatemalan small-scale agricultural systems, describe farmers’ perceptions of climate change and impacts, and document their adaptation efforts. Materials and methods. Structured surveys were carried out in households growing coffee or basic grains in Acatenango and Chiquimula landscapes, two climate change vulnerable landscapes, between June and July 2014. The research was based on farmers’ perceptions of changes in temperature and rainfall, the impacts related to these changes, and the adaptation actions implemented in response to perceived changes. Results. Results indicated that 95% of farmers perceived changes in climate, and 81% of them considered these changes to have negatively affected their production. Only 41% of farmers had implemented measures to adapt to these changes, mainly those farmers growing coffee. The implemented adaptation measures differed between landscapes , crops, and usefulness against perceived change with tree planting being the most common adaptation practice to buffer against temperature increases. Conclusion. In order to improve the adaptive response ofsmallholder farmers and to promote the use of practices that increase resilience, it is neecessaryto provide more technical, financial and political support to facilitate the adaptation of small farmers facing climate change.